Xenobiotic metabolizing enzymes and metabolism of anthelminthics in helminths - Cvilink, Viktor; Lamka, Jiri; Skálová, Lenka (Drug metabolism reviews, 2009)
Anthelminthics remain the only accessible means in the struggle against helminth parasites, which cause significant morbidity and mortality in man and farm animals. The treatment of helminthic infections has become problematic because of frequent drug resistance of helminth parasites. The development of drug resistance can be facilitated by the action of xenobiotic metabolizing enzymes (XMEs). In all organisms, XMEs serve as an efficient defense against the potential negative action of xenobiotics. The activities of XMEs determine both desired and undesired effects of drugs, and the knowledge of drug metabolism is necessary for safe, effective pharmacotherapy. While human and mammalian XMEs have been intensively studied for many years, XMEs of helminth parasites have undergone relatively little investigation, so far. However, many types of XMEs, including oxidases, reductases, hydrolases, transferases, and transporters, have been described in several helminth species. XMEs of helminth parasites may protect these organisms from the toxic effects of anthelminthics. In case of certain anthelminthics, metabolic deactivation was reported in helminth larvae and/or adults. Moreover, if a helminth is in the repeated contact with an anthelminthic, it defends itself against the chemical stress by the induction of biotransformation enzymes or transporters. This induction can represent an advantageous defense strategy of the parasites and may facilitate the drug-resistance development.
Keywords: biologický transport; systém (enzymů) cytochromů P-450; Biological Transport; glutathiontransferasa; Metabolic Detoxication, Phase I; cizopasní červi; léková rezistence; Cytochrome P-450 Enzyme System; Metabolic Detoxication, Phase II; Glutathione Transferase; biotransformace; Biotransformation; Anthelmintics; zvířata; Humans; Xenobiotics; xenobiotika; Species Specificity; I. fáze biotransformace; II. fáze biotransformace; Drug Resistance; Helminths; druhová specificita; anthelmintika; lidé; Animals